Physical and optical properties of SnO2 quantum dots prepared by sol-gel method / Nur Fadhli Shakirah Mohd Fauzi - Mohd Fauzi, Nur Fadhli Shakirah (2020)
Physical and optical properties are important characteristics of materials. Most metal oxide nanomaterials, such as, SnO2 nanomaterials exhibit bandgap narrowing, however, SnO2 quantum dots conversely exhibit band gap narrowing. It is important to understand this phenomenon at a more fundamental level. In this work, the reasons behind physical and optical properties is probed in terms of crystal structure, the role of surfactant and quantum mechanical effects of energy discretization in the materials. The samples were annealed at 350 oC and 450 oC for 1 h, 3 h, 5 h, and 24 h for the investigation of the different nanostructured SnO2 quantum dots. The crystallite size of SnO2 quantum dots using surfactant were found to decrease with calcination time. Crystal structural parameters were extracted via the Rietveld method and it was found that changes of both the a and c cell parameters were greatest in the crystallite size range of the nano region (100 nm and below). It was observed that there is a correlation between the crystallite size with the band gap of the nanomaterials. It is proposed that the band gap widening is due to the decrease in the hybridization of the SnO2 quantum dots energy levels resulting in more discrete energy levels and the widening of the band gap. This quantum effect may not be seen in other metal oxides with different electronic configurations and crystal structure.